INCORPORATING FOUR RESOURCES MODEL AND SONG LYRICS TO PROMOTE CRITICAL LITERACY PRACTICE IN AN EFL CLASSROOM - Nur Ijabah, - (2019)
Teks dipengaruhi oleh ideologi dan perspektif sosial-politik penulis. Oleh karena itu dalam melakukan kegiatan literasi, baik membaca dan menulis, siswa harus menganalisisnya melalui berbagai perspektif dan tidak menerima semua informasi begitu saja. Namun, praktik literasi dalam konteks EFL masih dilakukan terbatas pada mendiskusikan fitur linguistik dan memahami informasi dangkal teks. Dengan demikian, guru harus mengubah orientasi literasi dari literasi tradisional menjadi literasi kritis. Literasi kritis bergerak melampaui penguraian kata-kata menjadi menafsirkan kata-kata dan konteksnya untuk menyimpulkan perspektif sosial, politik, dan ideologis yang disajikan dalam teks. Penelitian ini dimaksudkan untuk menyelidiki penggabungan empat model sumber daya literasi kritis dan lirik lagu untuk mempromosikan praktik literasi kritis di sekolah menengah di Pamekasan. Diskusi teks dilakukan berdasarkan kerangka kerja fout resources model yang diusulkan oleh Luke dan Freebody (1999). Data diperoleh dari observasi kelas, wawancara kelompok, tanggapan tertulis siswa dan jurnal reflektif siswa dari aktivitas penyelidikan lirik lagu. Temuan menunjukkan bahwa penggabungan fout resources model dan lirik lagu membantu pengembangan kapasitas kritis siswa. Para siswa dapat mengenali pemilihan bahasa penulis lagu melalui kegiatan code breaking; mengembangkan berbagai perspektif melalui diskusi interpretasi lirik lagu dalam tahap membuat makna; memahami struktur dan fungsi sosial dari lirik lagu melalui tahap penggunaan teks secara fungsional; dan menantang nilai-nilai sosial seperti standar kecantikan dan fobia Islam melalui diskusi kritis lirik lagu. Terlepas dari tantangan dan keterbatasan, penelitian ini memberikan bukti kelayakan praktik literasi kritis dalam konteks EFL. Texts are influenced by the writer's ideology and social-political perspectives. Therefore in doing literacy activities, both reading and writing, students should analyze them through multiple perspectives and do not take all information for granted. However, literacy practice in EFL context is still limitedly conducted for breaking linguistic features and understanding surface information of the texts. Thus, teachers should change literacy orientation from traditional literacy into critical literacy. Critical literacy moves beyond decoding words to interpreting words and its context to conclude social, political, and ideological perspectives presented in the text. This study is intended to investigate the incorporation of four resources model of critical literacy and song lyrics to promote critical literacy practice in a secondary school in Pamekasan. The texts discussions were conducted based on the framework of four resources model proposed by Luke and Freebody (1999). The data were obtained from classroom observation, focus group interview, students' written responses and students' reflective journals of song lyrics investigation. The findings showed that the incorporation of four resources model and song lyrics help students' critical capacity development. The students were able to recognize the song writer's language choice through breaking codes activities; develop multiple perspectives through the discussion of song lyrics interpretation in the stage of making meaning; understand the structures and social function of song lyrics through the stage of using text functionally; and challenge the social values such as beauty standard and Islam phobia through critical discussion of song lyrics. Apart from challenges and limitations, this study provides evidence of the feasibility of critical literacy practice in EFL context.